Don’t Rub; It Will Be Evident- Corneal Topographic Changes In Patients With Vernal Keratoconjunctivitis (Indian Journal of Applied-Basic Medical Sciences, 2022)
Abstract Aim To study topographic findings in patients with established vernal keratoconjunctivitis (VKC). Materials and methods In a hospital based cross sectional study, 112 eyes of age group 11-22 years with established case of VKC were selected for topography. Result In 112 eyes with VKC; 69.64% (78 eyes) had significant history of eye rubbing. 14.28% (16 eyes) had Kmax values >=47.2D , 85.71%(96 eyes) had Kmax values =1.2D ; 80.36%(90 eyes) had I-S Difference
Keywords: Corneal topographic; vernal keratoconjunctivitis